Agenesis of third molars and associated factors in patients at an outpatient dental clinic - Silva-Castillo, Rocío Itzel (2025)
Objective: To determine the occurrence of third molar agenesis and associated factors in patients at an outpatient dental clinic in Morelos, Mexico. Materials and methods: Cross-sectional design based on a series of 295 digital panoramic radiographs, selected through consecutive sampling and evaluated using CS Imaging® software (Carestream Dental, Atlanta, GA, USA). Binary logistic regression analysis was performed using the SPSS v. 24 statistical package (IBM Corp., Armonk, NY, USA) to calculate odds ratios and 95% confidence intervals between agenesis and explanatory factors. Results: Agenesis was more prevalent in the maxillary third molars, with 59.3% (n = 175) in tooth 18 and 53.9% (n = 159) in tooth 28. In contrast, mandibular third molar agenesis was less frequent, with 46.8% (n = 138) in tooth 38 and 45.8% (n = 135) in tooth 48. The absence of two molars showed the highest occurrence, with 40.1% (n = 118) of cases. Age increased the probability of agenesis in tooth 18 (aOR = 1.74; 95% CI: 1.07-2.94) and 28 (aOR = 1.91; 95% CI: 1.13-3.21), while female sex was associated with a higher probability of agenesis in tooth 38 (aOR= 1.82; 95% CI: 1.17-3.06). Conclusion: Third molar agenesis is a common condition influenced by age and sex, suggesting the usefulness of these sociodemographic factors to anticipate patterns in different populations.